2002
DOI: 10.1093/intimm/dxf071
|View full text |Cite
|
Sign up to set email alerts
|

A CD18-dependent protein kinase C beta-mediated alternative cell death pathway of activated monocytes

Abstract: Activated monocytes become resistant to numerous death stimuli including death receptors. Given that the uncontrolled activation of monocytes/macrophages and their persistence can lead to severe inflammatory conditions, it is critical to define the pathways that control their elimination. We previously reported that ligation of HLA-DR molecules on peripheral blood-derived monocytes induces their death. To investigate the mechanisms of HLA-DR-mediated death in monocytes, we used the THP-1 monocytic cell line as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
1
12
1
Order By: Relevance
“…For APCs, it has recently been established that MHC class II can associate with other cell receptors. For instance in B cells, MHC class II molecules associate with CD79a/CD79b, CD20, and CD19, and in monocytes, a CD18/MHC class II complex has been identified [58,[67][68][69][70]. Which molecules associate and transduce the MHC class II-mediated signaling in activated T cells remains to be investigated, however.…”
Section: Mhc Class II Ligation-induced Intracellular Signalingmentioning
confidence: 99%
“…For APCs, it has recently been established that MHC class II can associate with other cell receptors. For instance in B cells, MHC class II molecules associate with CD79a/CD79b, CD20, and CD19, and in monocytes, a CD18/MHC class II complex has been identified [58,[67][68][69][70]. Which molecules associate and transduce the MHC class II-mediated signaling in activated T cells remains to be investigated, however.…”
Section: Mhc Class II Ligation-induced Intracellular Signalingmentioning
confidence: 99%
“…Similarly, the activation of PKC-b 1 /b 2 was reported to induce the HLA-DR-mediated apoptotic cell death of THP-1 monocytic cells (Castaigne et al, 2002). This PKC-b 1 /b 2 -dependent HLA-DRmediated THP-1 cell apoptosis resulted from the activation of intrinsic caspase-dependent apoptotic signaling, and was independent of extrinsic (receptor-dependent) caspase-8-mediated apoptotic signaling (Castaigne et al, 2002). This study demonstrated that the treatment of the CD14 þ monocytes with H-PMA triggered the mitochondrial translocation of PKC-b 2 .…”
Section: Discussionmentioning
confidence: 90%
“…The treatment with 50 nM PMA was found to induce the apoptosis of human U-937 monocytic cells through eliciting PKC-b 2 -and intrinsic (mitochondria-dependent) caspasedependent apoptotic signaling (Ito et al, 2001). Similarly, the activation of PKC-b 1 /b 2 was reported to induce the HLA-DR-mediated apoptotic cell death of THP-1 monocytic cells (Castaigne et al, 2002). This PKC-b 1 /b 2 -dependent HLA-DRmediated THP-1 cell apoptosis resulted from the activation of intrinsic caspase-dependent apoptotic signaling, and was independent of extrinsic (receptor-dependent) caspase-8-mediated apoptotic signaling (Castaigne et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…Several functional effects have been reported in response to the crosslinking of MHC-II molecules such as homotypic aggregation of the cells (Mourad et al, 1990;Fuleihan et al, 1992;Kansas et al, 1992;Lehner et al, 2003), cytokine production (Homfeld et al, 1990;Mourad et al, 1992;Altomonte et al, 1993;al Daccak et al, 1994;Mehindate et al, 1994aMehindate et al, , b, 1995Rink et al, 1994;Trede et al, 1995;Bernatchez et al, 1997;Coral et al, 1997;Lei et al, 2001;Lehner et al, 2003;Meguro et al, 2003), upregulation of CD80 (Koulova et al, 1991), proliferation (Cambier et al, 1987;Lei et al, 2001, reviewed in Scholl andGeha, 1994;al Daccak et al, 2004), and also apoptosis (Truman et al, 1994;Thibeault et al, 1999;Bertho et al, 2002;Castaigne et al, 2002;Bains et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is a possible explanation for another obstacle in MHC-II signal transduction research: The results of MHC-II crosslinking depend not only on the MHC-II carrying cell type used (Guo et al, 1999), but also on its maturation and/or activation state (Coral et al, 1997;Lehner et al, 2003). For example, most apoptotic influences of anti-HLA-DR antibodies are strongly enhanced only in activated or mature cells if it is detected at all (Truman et al, 1994;Bertho et al, 2002;Castaigne et al, 2002). This is understandable considering that cells of different maturation and activation states express varying surface molecules that may in each case serve as accessory proteins for MHC-II.…”
Section: Introductionmentioning
confidence: 99%